The Role of Satirical TV Shows on Social Media Sites in Shaping Political Trends among University Students (Eurasian Journal of Media and Communications, 2024)
The research aims to find out the students ' point of view on the role of satirical TV programs on social media sites in shaping their political trends, the researcher followed the descriptive analytical approach due to its suitability for the research objectives and used the survey method using the questionnaire form as the main tool for data collection, and scientific investigation the researcher used the intentional sample, which is a type of samples that the researcher chooses the vocabulary in a controlled manner to perform the purpose of the research, where the intentional sample was represented by the students of Imam Al-kadhim College of Islamic sciences, male and female, numbering (300) students, and then empty the form into tables and calculate their repetitions and percentages and analyze their results